Relativistic Convergent Close-Coupling method for excitation and ionization processes in electron collisions with atoms and ions - Fursa, Dmitri; Bray, Igor (Institute of Physics Publishing Ltd., 2009)
We have used relativistic Convergent Close-Coupling method to perform calculations of electron scattering from cesium and gallium atoms. Differential, integrated and ionization cross sections and spin asymmetries have been calculated from 1 to 500 eV and compared with available experimental data and results of other calculations.